The outcome of Flexor Tendon Repair based on the number of core suture, mechanism and zone of injury in Erbil - Hamzah, Shams Ramadhan; Fattah, Jalal Hamasalih (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Principles of surgical treatment of flexor tendon injuries include early primary repair with a strong core stitch combined with an epitendinous suture. This study aimed to evaluate the outcomes of primary flexor tendon repair according to the mechanism, zone of injury and number of core sutures. Methods: This study was conducted in Erbil from May 2013 till March 2015. Injured flexor tendons were repaired for 121 patients. The patients were followed up for six months. We used the Strickland scoring system to evaluate the results. Results: Sharp tools represented the main cause of trauma 68.6%, excellent results were found in 51.8% of cases with a sharp injury. The worst results were obtained in zone II with 44.7% fair to a poor result. Excellent results found in 43.4% with four strand core sutures while 24.4% in two strand core sutures (P ˂0.01). Conclusion: Four strand core sutures have the better result with a low rate of tendon rupture than two strand core sutures. Sharp injuries had better results than crush injuries. The zone with worst results was zone II.